Methylene-bridge tryptophan fatty acylation regulates PI3K-AKT signaling and glucose uptake - Hu, Song-Hua; He, Xia-Di; Nie, Ji; Hou, Jun-Li; Wu, Jiang; Liu, Xiao-Yan; Wei, Yun; Tang, Hui-Ru; Sun, Wen-Xing; Zhou, Shu-Xian; Yuan, Yi-Yuan; An, Yan-Peng; et al. (Cell reports (Cambridge), 2022)
Protein fatty acylation regulates numerous cell signaling pathways. Polyunsaturated fatty acids (PUFAs) exert a plethora of physiological effects, including cell signaling regulation, with underlying mechanisms to be fully understood. Herein, we report that docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) regulate PI3K-AKT signaling by modifying PDK1 and AKT2. DHA-administered mice exhibit altered phosphorylation of proteins in signaling pathways. Methylene bridge-containing DHA/EPA acylate δ1 carbon of tryptophan 448/543 in PDK1 and tryptophan 414 in AKT2 via free radical pathway, recruit both the proteins to the cytoplasmic membrane, and activate PI3K signaling and glucose uptake in a tryptophan acylation-dependent but insulin-independent manner in cultured cells and in mice. DHA/EPA deplete cytosolic PDK1 and AKT2 and induce insulin resistance. Akt2 knockout in mice abrogates DHA/EPA-induced PI3K-AKT signaling. Our results identify PUFA’s methylene bridge tryptophan acylation, a protein fatty acylation that regulates cell signaling and may underlie multifaceted effects of methylene-bridge-containing PUFAs. [Display omitted] •The methylene-bridge-containing polyunsaturated fatty acids EPA and DHA modify proteins•Tryptophan is a site of posttranslational modifications by polyunsaturated fatty acids•EPA and DHA activate AKT signaling by modifying PDK1 and AKT2•EPA and DHA promote glucose uptake but induce insulin resistance Hu et al. find that methylene-bridge-containing polyunsaturated fatty acids EPA and DHA covalently modify surface tryptophan of membrane-targeting proteins, including PDK1 and AKT2, and recruit them to the cytoplasmic membrane to activate AKT signaling. The EPA and DHA actions facilitate glucose uptake but can also induce insulin resistance.